Design Principles for a Community Informatics–Driven Data Integration Platform: A Conceptual Architecture for the Trefoil Guild Melaka - Abdul-Aziz, Azlianor; Sulong, Muhammad Suhaizan; Bohari, Nor Mas Aina Md; Abdullah, Rosmiza Wahida; Kasim, Amir Syarifuddin; Ahmad, Sabrina; Sanusi, Nurazlina Md. (Advances in Social Sciences Research Journal, 2025)
Community-based organisations increasingly rely on digital systems to support membership coordination, activity tracking, and capability-building programs. However, small volunteer-led associations often lack platforms that reflect their community values, participatory practices, and user-centered needs. This paper proposes a conceptual data-integration architecture for the Trefoil Guild Melaka, guided by contemporary perspectives in Community Informatics, Participatory Information Systems, and User-Centered Design. Adopting a conceptual modeling approach rather than empirical evaluation, the paper synthesises socio-technical frameworks to outline an integrated platform comprising membership, activity-tracking, and capability-building modules. The contribution is both theoretical and methodological, demonstrating how socio-technical principles can inform platform design for grassroots organisations and support digital inclusion, collective agency, and participatory engagement. The discussion also highlights implications for digital empowerment strategies, participatory system development, and future implementation pathways, emphasizing how carefully conceptualised architectures can provide community-driven organisations with sustainable trajectories for digital transformation.